Diurnal Pattern and Estimation of Global Solar Radiation in East Coast Malaysia - Mahendran, Samykano; Lee, Giok Chui; Shahrani, Anuar; R. A., Bakar; K., Kadirgama; Amir, Abdul Razak; Sharma, K. V. (2013)
The solar radiation study have been undertaken at Pekan campus (3.5ºN, 103.4ºE), Faculty of Mechanical Engineering, University Malaysia Pahang to utilize solar energy in east coast of Malaysia. The knowledge of the daily variation of global solar radiation is a necessity at the particular locality to consider the feasibility of solar energy utilisation. Hence, the diurnal patterns of global solar radiation were obtained using measured data from weather station which was installed at the site for three years (2011 – 2013). The patterns have been divided into five conditions such as clear sky, partially cloudy, fully cloudy, afternoon rain, and northeast monsoon season day. It was observed that on a clear sky day in Pekan, the maximum solar insolation was 939 W/m2 and total solar energy received was 6.51 kWhr/m2. In contrast, on a fully cloudy day the maximum solar insolation was only 30 W/m2 and total solar energy received was 0.35 kWhr/m2. Besides that, the empirical models were developed to estimate the monthly average daily global solar radiation on a horizontal surface with Pekan meteorological station data. Subsequently, the models were evaluated using statistical analysis. Based on analysis results, Eq. (13) and Eq. (15) models are proposed to estimate monthly average daily global solar radiation for Pekan. The present paper describes on advance understanding of daily variation global solar radiation in east coast Malaysia whereby it has significance for designing a solar system. Lastly, the developed Angstrom’s modified linear models are highly recommended to be used to estimate the monthly average daily global solar radiation in Pekan, Pahang and location with similar solar radiation patterns in east coast Malaysia.